VIRAL MARKETING SEBAGAI MEDIA PEMASARAN SOSIAL DALAM MENDONGKRAK KESADARAN MASYARAKAT UNTUK BERPERAN AKTIF DAN BERGABUNG DENGAN ORGANISASI NON PROFIT/NIARLABA - Yoshua Glennardo (Universitas Trunojoyo Madura, 2016)
In the meantime, people’s concern for each other and environment has been decreased so drastically. People are become individualistic because people are race each other to become succed. People which good at business are thinking of themselves without any concern in the environment. Right now in Indonesia there are so much non profit organization that keep the environment safe. Not only the environment, they care about health, education, norm, etc. To aware participating in this non profit organization, a marketing strategy that effective are neede. Viral mraketing will be the marketing strategy that can be used to aware people be active and resolve that social problem.